Undifferentiated pleomorphic sarcoma of the adrenal gland: a case report and literature review - Xiaochuan, Gong; Wei, Zhao; Chaoyong, Yuan; Yu, Zhou; Huayong, Jian; Na, Yin; Xike, Luo; Jian, Lei; Yan, Wang (Frontiers in Oncology, 2024)
Undifferentiated pleomorphic sarcoma (UPS) is a rare type of tumor, and UPS originating in the adrenal gland is even rarer. Up to now, there have been no reports in English literature of UPS originating from the adrenal gland. This case report presents a 44-year-old female patient with UPS of the adrenal gland, who has shown no signs of recurrence or metastasis half a year after undergoing resection of a left adrenal tumor. A retrospective analysis of the patient’s diagnosis and treatment process is conducted, with the aim of providing a reference for the diagnosis and treatment of adrenal UPS.